New-dialect formation : the inevitability of colonial Englishes - Trudgill, Peter (Edinburgh University Press, 2004)
This volume presents a new and controversial theory about dialect contact and the formation of new colonial dialects. It examines the genesis of Latin American Spanish, Canadian French and North American English, but concentrates on Australian and South African English.